Acquisition is expected to spur growth of EKK Eagle Industry. Issue 12 (December 2015) - Unknown
Abstract : EKK Eagle Industry, which has supplied automotive and industrial sealing and control products for more than half a century, has announced that it has acquired ABC Technology in France, a global producer of electromagnetic subassemblies.